Gambaran Kebahagiaan Ibu Tunggal yang Bekerja - Tiara, Ade; Islamia, Intan; Reza, Faisal Adnan (Universitas Muhammadiyah Metro, 2025)
Working is a necessity for single mothers to meet the economic needs of their families. However, this often leads to conflicts between work and family responsibilities, resulting in stress that negatively impacts their health, parenting, and work productivity. Nevertheless, work can also be a source of happiness. The objective of this study is to explore the factors and aspects that describe the happiness of working single mothers, with a focus on the role of work in their lives. This research employs a qualitative descriptive method, with data collection conducted through semi-structured interviews and field notes. Data analysis was performed using Nvivo 12 Plus to draw conclusions. The study involved three participants, selected using purposive sampling techniques. The findings reveal that the sources of happiness for working single mothers are reflected in their engagement in daily activities, positive social relationships, and the achievement of life goals. Furthermore, the highest factors influencing the happiness of working single mothers are external social life factors and internal satisfaction in the present moment. Conversely, factors such as age and educational level were found not to contribute to their happiness. This study concludes that work can significantly influence the happiness of single mothers. For single mothers, work plays a role in diverting negative emotions and fostering feelings of pride, joy, peace, and self-confidence.